EFEKTIVITAS PENERAPAN MODEL QUANTUM TEACHING TERHADAP HASIL BELAJAR SISWA MAS MAMBAUL ULUM 2 KOREK - Safiudin, Safiudin; Asriati, Nuraini; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe General purpose of this research is to know the effectiveness of implementation of the Model of Quantum teaching lessons in economic learning class X The private Madrasah Aliyah mambaul ulum 2 matches Sungai Ambawang.The Research methods used in this study are exprimentary. Exprimentary research is a method of study that investigates the possibility of causal relationship, then by the method of experimentation, researchers intend to reveal there is no influence of the model of quantum teaching learning in students of Class X Mas Mambaul ulum 2 matches.From the results of data analysis obtained the average value of the test post control class of 68.25 and the Post test class Expritment value of 78,25. The result of the calculation of the hypothesis test is known T-count for the student learning result is-9,952 with probability (SIG) 0.00 < 0.05 then Ho rejected and Ha accepted. This means that there is a significant influence on the modeling of quantum teaching learning to learn students. Based on the result of the size of effect obtained by the results of a value of 13.75 â‰¤ 0.8, means the test results of the implementation of quantum teaching models are included in the high criteria. It can be concluded that the implementation of a quantum teaching learning model is effective in enhancing the economic learning outcomes of class X MAS Mambaul Ulum 2Keywords: The learning Model of Quantum teaching, learning outcomes, economic subjects,